Analysis of Properties of Trace Aluminium Complex Solution with Dibromo-o-Carboxy-Chlorophosphonazo - Gao, Hong-Wen; Yu, Lin-Qian (Asian Journal of Chemistry, 2010)
The two reactions were both sensitive between aluminium(III) and dibromo-o-carboxy-chlorophosphonazo (DBKCPA) at pH 7. The β-correction dual-wavelength spectrophotometric method was applied to the determination of properties of aluminium complex solutions because it was able to eliminate the interference of excess ligand in the reaction system. The multi-coordination reaction was found in such a complex system because the complex ratio of Al(III) to DBKCPA was equal to 1 : 2. In addition, the investigation still brought out the easy determination of the stepwise real molar abs. orptivity (ε) and the stepwise or cumulative stability constant (K) of AI-DBKCPA complex.